Metalloproteinases in Inflammatory Bowel Diseases - Marônek M; Marafini I; Gardlík R; Link R; Troncone E; Monteleone G (Dove Medical Press, 2021)
Martin Marônek,1,* Irene Marafini,2,* Roman Gardlík,1 René Link,3 Edoardo Troncone,2 Giovanni Monteleone2 1Institute of Molecular Biomedicine, Faculty of Medicine, Comenius University in Bratislava, Bratislava, 81108, Slovakia; 2Department of Systems Medicine, University of Rome “Tor Vergata”, Rome, 00133, Italy; 3Institute of Experimental Medicine, Faculty of Medicine, University of Pavol Jozef Šafárik, Košice, 040 11, Slovakia*These authors contributed equally to this workCorrespondence: Giovanni MonteleoneDipartimento di Medicina dei Sistemi, Università di Roma “Tor Vergata”, Via Montpellier 1, Rome, 00133, ItalyTel +39 06 20903702Fax +39 06 72596391Email Gi.Monteleone@Med.uniroma2.itAbstract: Inflammatory bowel diseases (IBD) are chronic inflammatory diseases of the gastrointestinal tract, encompassing two main disorders: Crohn’s disease (CD) and ulcerative colitis (UC). In both these pathologies, excessive and local immune response against luminal antigens promotes a pathological process leading to various degrees of gut damage. Matrix metalloproteinases (MMPs) are a family of neutral proteases with the ability to degrade all components of extracellular matrix. In physiological conditions, MMPs are produced at very low level and generally in the latent form and are involved in the normal tissue turnover. Their function is inhibited by tissue inhibitors of metalloproteinases (TIMPs). However, in inflamed tissue of IBD patients, MMPs are produced in excess and/or the activity of TIMPs is not sufficient to block MMPs, thereby making a major contribution to the IBD-related mucosal degradation. In this review, we summarize the available evidence on the expression and role of MMPs in IBD.Keywords: tissue inhibitor of metalloproteinases, Crohn’s disease, ulcerative colitis, intestinal inflammation